SERUM BIO-CHEMICAL INDICES IN CAPTIVE BONNET MACAQUES (Macaca radiata) - M. Palanivelrajan; M.G. Jayarthangaraj; R. Sridhar; M. Parthiban; R. Thirumurugan (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A clinical parameter study was conducted to file the reference serum bio-chemical values of Bonnet macaques (Macaca radiata) reared under captivity. The animals were chemically restrained and six blood samples (3 males and 3 females) were collected from the saphenous vein and processed. In this study, the mean ± S.E. of estimated value of serum biochemical profiles were close to the normal range reported earlier. But, serum glucose level was less and serum level of phosphorus was comparatively high.